2022
DOI: 10.1038/s41467-022-31080-2
|View full text |Cite
|
Sign up to set email alerts
|

A multi-ethnic polygenic risk score is associated with hypertension prevalence and progression throughout adulthood

Abstract: In a multi-stage analysis of 52,436 individuals aged 17-90 across diverse cohorts and biobanks, we train, test, and evaluate a polygenic risk score (PRS) for hypertension risk and progression. The PRS is trained using genome-wide association studies (GWAS) for systolic, diastolic blood pressure, and hypertension, respectively. For each trait, PRS is selected by optimizing the coefficient of variation (CV) across estimated effect sizes from multiple potential PRS using the same GWAS, after which the 3 trait-spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 55 publications
4
42
2
2
Order By: Relevance
“…Given the higher frequency of White participants in the MVP, we hypothesized that the PRS would perform somewhat better in this population. Although our finding was unexpected, a previous study assessing the performance of the BP PRS in Black and White CARDIA participants showed that the Black participants in the high PRS percentiles developed hypertension earlier than the White participants in higher PRS percentiles when compared to their counterparts in lower PRS percentiles [ 37 ]. Given the limited number of studies with this type of data, it is difficult to determine whether this might be a statistical anomaly or whether genetic susceptibility could be more deterministic in Black participants.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Given the higher frequency of White participants in the MVP, we hypothesized that the PRS would perform somewhat better in this population. Although our finding was unexpected, a previous study assessing the performance of the BP PRS in Black and White CARDIA participants showed that the Black participants in the high PRS percentiles developed hypertension earlier than the White participants in higher PRS percentiles when compared to their counterparts in lower PRS percentiles [ 37 ]. Given the limited number of studies with this type of data, it is difficult to determine whether this might be a statistical anomaly or whether genetic susceptibility could be more deterministic in Black participants.…”
Section: Discussioncontrasting
confidence: 55%
“…Furthermore, because this study was conducted in a sample of two races of participants, we were able to evaluate the performance of the PRS in non-White participants, which have been underrepresented in genomics research. The PRSs used in this study were derived from the summary statistics of a large, multi-ancestry GWAS that were tested among 10,314 diverse participants using a novel approach and evaluated in 40,201 individuals [ 37 ]. Representing some of the first BP PRSs generated in diverse samples, our study demonstrates strong associations in non-White participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, we found in our recent work using summary statistics from large GWAS (hundreds of thousands of individuals) that PRS constructed based on GWAS in a population of a predominately European ancestry tend to generalize to Hispanics/Latinos, often with similar or only slightly attenuated performance. 70 , 71 If PRS have attenuated performance, we expect that estimated effect sizes will be biased towards the null compared to the effect sizes of optimal PRSs, rather than lead to false detections of associations. Second, the OSA GWAS that we used was based on ICD codes from a health care system, and is likely limited by under diagnosis of OSA.…”
Section: Discussionmentioning
confidence: 99%